Biochemical and physiological analysis in carrot seeds from different orders of umbels - Silva, Patricia; Sekita, Marcelo; Dias, Denise; Nascimento, Warley (Revista Ciência Agronômica, 2016)
In carrot seed production, harvesting of the umbels is generally staggered, or sometimes the whole plant is harvested with the umbels at different stages of maturation; in that case, there is a risk of harvesting immature seeds and of losses due to natural dehiscent, or to physiological deterioration as a result of unfavourable environmental factors. The present study aimed to evaluate the physiological and biochemical changes related to the maturation of ‘Planalto’ carrot seeds from diferent umbels. The samples were collected 120 days after anthesis, with the primary, secondary and tertiary umbels being harvested separately. Seeds were analysed for germination, first count and germination rate, at temperatures of 25 °C (optimum) to 35 °C (adverse), as well as for emergence in the greenhouse and the emergence rate. Analyses were also carried out of the enzymes peroxidase (POX), ascorbate peroxidase (APX), catalase (CAT) and superoxide dismutase (SOD), and of the total protein. Seeds obtained from the primary and secondary umbels displayed a higher rate of germination than from the tertiary umbels, with the seeds from the primary umbels showing high activity for peroxidase, catalase and superoxide dismutase, and low activity for the enzyme ascorbate peroxidase.